2011
DOI: 10.1016/j.virol.2010.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Amino acids contributing to antigenic drift in the infectious bursal disease Birnavirus (IBDV)

Abstract: We examined the effect of amino acids 222 and 254 on antigenicity of the variant Del-E strain of infectious bursal disease virus (IBDV). Using molecular epidemiology, we identified a virus designated as Del-E-222 that was identical to Del-E except for alanine at position 222. A second virus was generated using reverse genetics of the Del-E backbone to create Del-E-254 that contained an asparagine at amino acid 254. The Del-E-222 and Del-E-254 viruses were tested for their ability to escape neutralizing immunit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
55
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(70 citation statements)
references
References 21 publications
1
55
0
1
Order By: Relevance
“…Glutamic acid is characterized by negatively charged (acidic) R group, whereas the R group in alanine is nonpolar (hydrophobic). It is probable that this change from negative charge to nonpolar may modify the protein folding or the interaction with other molecules that may change the topography of the neutralizing epitopes that may lead to vaccination failure [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Glutamic acid is characterized by negatively charged (acidic) R group, whereas the R group in alanine is nonpolar (hydrophobic). It is probable that this change from negative charge to nonpolar may modify the protein folding or the interaction with other molecules that may change the topography of the neutralizing epitopes that may lead to vaccination failure [19]. …”
Section: Discussionmentioning
confidence: 99%
“…Despite the regions under purifying selection being wider than the hydrophilic peaks, this is most probably a consequence of a hitchhiking effect commonly observed in regions under strong functional constraint (Barton, 2000). Considering that any change within these hydrophilic regions may potentially cause a change in the antigenic features of an isolate (Letzel et al, 2007;Jackwood & Sommer-Wagner, 2011), a strong purifying selection pattern as observed in this study could indicate a lack of a selection-driven immune escape in the evolutive pathway of the virus. Partial VP2 sequences have been widely used in routine diagnosis and epidemiological studies worldwide (Jackwood & Sommer-Wagner, 2011).…”
Section: Discussionmentioning
confidence: 65%
“…Considering that any change within these hydrophilic regions may potentially cause a change in the antigenic features of an isolate (Letzel et al, 2007;Jackwood & Sommer-Wagner, 2011), a strong purifying selection pattern as observed in this study could indicate a lack of a selection-driven immune escape in the evolutive pathway of the virus. Partial VP2 sequences have been widely used in routine diagnosis and epidemiological studies worldwide (Jackwood & Sommer-Wagner, 2011). Nonetheless, in order to accurately infer an IBDV phenotype, genome fragments including segments A and B need to be analysed.…”
Section: Discussionmentioning
confidence: 79%
“…Sometimes, T residue at position 222 of VP2 has also been observed in a few variant strains, including DEL-E, GLS, and GA988 (Jackwood and Sommer-Wagner, 2011;Letzel et al, 2007). Recently, a new occurring mutation P222S was observed in Belg strain (Letzel et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…A single substitution at position 222 (P222S or A222T) was able to alter the antigenic pattern of IBDV because an S or T residue at position 222 is the essential part of the epitope that reacts with MAb 67 (Letzel et al, 2007). Recently, a natural mutation T222A was shown to allow the Del-E strain to break through the maternal immunity induced by parenteral vaccination (Jackwood and Sommer-Wagner, 2011).…”
Section: Discussionmentioning
confidence: 99%